Lissencephaly-1 is a context-dependent regulator of the human dynein complex - Janina Baumbach (eLife, 2017)
The cytoplasmic dynein-1 (dynein) motor plays a central role in microtubule organisation and cargo transport. These functions are spatially regulated by association of dynein and its accessory complex dynactin with dynamic microtubule plus ends. Here, we elucidate in vitro the roles of dynactin, end-binding protein-1 (EB1) and Lissencephaly-1 (LIS1) in the interaction of end tracking and minus end-directed human dynein complexes with these sites. LIS1 promotes dynactin-dependent tracking of dynein on both growing and shrinking plus ends. LIS1 also increases the frequency and velocity of processive dynein movements that are activated by complex formation with dynactin and a cargo adaptor. This stimulatory effect of LIS1 contrasts sharply with its documented ability to inhibit the activity of isolated dyneins. Collectively, our findings shed light on how mammalian dynein complexes associate with dynamic microtubules and help clarify how LIS1 promotes the plus-end localisation and cargo transport functions of dynein in vivo.